Review Penggunaan Obat Rawat Jalan Peserta Askes Sosial di RSMH Palembang selama Tahun 2007 Pemberdayaan Masyarakat Bidang Kesehatan di Era Otonomi Daerah - Sarmalina S., Sonlimar M. (Berita Kedokteran Masyarakat (BKM), 2008)
Background: Since  1987 PT Askes  has  been  implementing  the  drug  usage  guideline which  is called DPHO (Daftar dan  Plafon Harga Obat).In  order    to encourage  drug  services  efficiently  and  related  to medical  needs. In addition    PT Askes has got benefits in medicine expenses that can lower  it up to 40%. Although it has    better guidence  as  long  as  implementations without being  control continuously      the aim  of  it      can  be  far  from  hope. Through  this study we want  to  examine  how extent  the  drug  usage  in  social  health  insurance.Method:  In  this  paper we  used  cross-sectional  study,  using entry  data  base  prescriptions      from  the  entire social  health  insurance  participant  related  in  to  the  first  care outpatient  and advanced  care outpatient. All of  the patients originally  based on  polyclinics hospital  services  in RSMH during  2007. All  of prescriptions we used  as data  resources. All  these data were  observed  and  analyzed  performed  in  descriptive and  tabulation.Results: The  result of  this  study  shows  that we  got 140.256  pieces of  per  encounter during  2007 with  total cost Rp10.657.075.126,00.  The  average  cost  per  encounter  is Rp75.983,00    range    from     Rp231,00  to Rp5.151.227,00. The  average number  of drug  per encounter  is 4,4  and  the  percentage drug  used of  antibiotics is  10,81%.Conclusion: This  study comes  to conclusion  that  the  prescriptions  costs    in social  health  insurance  outpatient was  high  enough.  It  is  cost  by    certain  prescriptions,  polifarmacy,  and  diverse    drugs  usage  in  overuse prescribing  category such  as vitamin  neurotropic and  drug used  in AH2    receptor  blocker    like    as  ranitidin  that has    been    prescribed    for alleviating   gastrointestinal  effect.Keywords:  drug  utilities, social  health  insurance,  health care,  outpatient